Effects of a sprint and plyometric warm-up protocol on vertical jump height and power in adolescent fe-male volleyball players. A randomized crossover study - Mancilla, C. S.; Hood Maldonado, K.; Hebel Lorca, M.; Castro Pérez, J.; Muñoz Albarrán, P.; Martínez-Lema, D.; López Pinilla, J. P.; Guede-Rojas, F. (Retos: nuevas tendencias en educación física, deporte y recreación, 2023)
The purpose of this study was to compare the immediate effects of a plyometric warm-up protocol (PWU) and a sprint warm-up protocol (SWU) on jumping performance in female volleyball players aged 14-16 years. Through a cross-over experimental design, 18 female players were randomly divided into two groups, each receiving both warm-up protocols (PWU and SWU). Before and after each protocol, height and jumping power were evaluated in squat jump (SJ), countermovement jump (CMJ), and Abalakov (ABK) tests using the DM jump® contact mat. Both warm-up protocols significantly improved SJ, CMJ, and ABK performance (p<.05), although mainly for jump height. The comparison between both warm-up protocols in the post-test showed no significant differences (p>.05), although the greatest percentage increase in jump height and power was obtained with the SWU. The ANOVA showed significant differences in group 1 (initially assigned to PWU) for all tests except for CMJ and ABK power. In group 2 (initially assigned to SWU), the ANOVA also showed significant differences, except for SJ and CMJ power. It is concluded that both warm-up protocols improve jump height and power; however, SWU shows a more favorable trend than PWU. From a practical perspective, the preliminary findings of this pilot study can provide useful guidelines for the warm-up process; however, further randomized controlled studies with adequate statistical power are required for more robust conclusions.